Encyclopedia of cyber behavior - Yan, Zheng 1958- (Information Science Reference, 2012)
"This book offers a complete look into the field of cyber behavior, surveying case studies, research, frameworks, techniques, technologies, and future developments relating to the way people interact and behave online" - Provided by publisher